First, try to see if you can cancel out any of the variables by adding the equations.
4x+2y-1 also equals 4x+2y=1
(4x+2y=1)(2) = 8x+4y=2
now, add the two equations and see the y cancel out.
Plug this number back into the equation (any of those two) and find y.
i still do see how you got that answer i got 2x-4y=7 ,4x+2y=-1. 6x+6y=6 isn't that how you do it please help understand better
the purpose oft using addition here is to add them in such a way so that one of the variables will cancel out
leave the first equation alone
2x-4y=7, multiply the second by 2
8x+4y=-2, now add them
10x + 0 = 5
x = 1/2
back in the first....
You just added them to get 6x+6y=6
Even though that new equation is valid and true it gets you nowhere.